Gingival inflammation assessment: Image analysis - Hema Seshan; M Shwetha (Wolters Kluwer Medknow Publications, 2012)
Background: Gingival inflammation may be caused by injury or plaque-related disease and reduction in inflammation can be a useful indicator of gingival recovery. There has been little research on development of non-index method to measure gingival condition. The study aimed to investigate the quantitative analysis of gingival swelling and color characteristics of gingiva by digital images before and after treatment of individual patients. Material and Methods: Twenty volunteers with gingival inflammation were recruited and digital images were taken. Duplicate measurements were made on the first visit by the same examiner. At a subsequent visit (1 month) following scaling and root planing, second images were taken. Gingival changes were determined by assessing redness and tooth surface area visible between the level of the inter-proximal papillae and the gingival margin. Results: Significant difference was found between the pre-operative and post-operative photographs with regard to swelling and gingival redness. Conclusion: Thus this method aids in quantitative analysis of swelling and color characteristics of gingiva by digital images may become a valuable, objective, practicable non-index and inexpensive evaluation procedure of gingival inflammation.